The Shiga toxin 2 production level in enterohemorrhagic Escherichia coli O157:H7 is correlated with the subtypes of toxin-encoding phage - Ogura, Yoshitoshi (Sci Rep, 2015)
Enterohemorrhagic E. coli (EHEC) causes diarrhea and hemorrhagic colitis with life-threatening complications, such as hemolytic uremic syndrome. Their major virulence factor is Shiga toxin (Stx), which is encoded by bacteriophages. Of the two types of Stx, the production of Stx2, particularly that of Stx2a (a subtype of Stx2), is a major risk factor for severe EHEC infections, but the Stx2 production level is highly variable between strains. Here, we define four major and two minor subtypes of Stx2a-encoding phages according to their replication proteins. The subtypes are correlated with Stx2a titers produced by the host O157 strains, suggesting a critical role of the phage subtype in determining the Stx2a production level. We further show that one of the two subclades in the clade 8, a proposed hyper-virulent lineage of O157, carries the Stx2 phage subtype that confers the highest Stx2 production to the host strain. The presence of this subclade may explain the proposed high virulence potential of clade 8. These results provide novel insights into the variation in virulence among O157 strains and highlight the role of phage variation in determining the production level of the virulence factors that phages encode.